Medium is a weapon : bias in crisis situations - Delić, Amela (Array, 2020)
This paper analyzes the ways in which the media can be abused to foster the most extreme political propaganda using the example of the former Socialist Federal Republic of Yugoslavia. After having propagated social values such as unity, harmony, brotherhood and anti-fascist heritage, in the late 1980s Serbian and Croatian media came under control of nationalists who manipulated them into propagating hatred, nationalism and xenophobia. In Bosnia and Herzegovina, such practice followed the outbreak of the Bosnian war and resulted in several media outlets which took the same course of action. Some media outlets will fully endorse McLuhan’s idea of technical intermediaries as modern weapons and even go one step further in their warlike messages than the political parties that formed them. The most striking examples are Bosnian-based TV Pale, Croatian daily newspaper Vjesnik and Serbian newspaper Politika (especially the Echoes and Reactions newspaper section). With their actions such media will confirm that the most dangerous form of media bias is precisely propaganda bias as defined by Denis McQuail. Its destructive power is illustrated on the example of the bloody Yugoslav break-up fueled by their spreading of misinformation.